Pharmaceutical Waste Management An Overview - Kadam, Atul; Patil, Shitalkumar; Patil, Sachin; Tumkur, Anil (Indian Journal of Pharmacy Practice)
Introduction: Medication disposal is an alarming issue today and gaining more and more awareness from the healthcare professionals as well as consumers. Pharmacists have the potential to be on the forefront of this movement as a healthcare professionals and pharmacists are in an admirable position to educate patients about safe drug disposal. Proper patient counselling on safe medication disposal can make a significant difference to public health and the environment. The knowledge on method of disposal of unused medicines is equally important as that of consumption of medicines. Objective: This article aims to provide a background, the importance and significance of proper medication disposal, describe the correct methods to dispose of unwanted and expired medications. Method: The information about methods of proper disposal as well as consequence of improper disposal was collected by extensive literature survey of all available resources. Conclusion: Till date, researchers have acknowledged many human and veterinary pharmaceutical compounds at serious concentrations in drinking water resources and they are a major contributor to environmental pollution. Emphasis is also given on pharmacist role in proper disposal of unwanted and expired medicine makes a significant impact on the environment as well as it prevents accident, poisoning and intentional violence. So it will lead to the welfare of society and trudge towards goal of 2020 health for all.
Keywords: Pharmaceutical Waste Management; Medication disposal; Patient education; Pollution